Pengembangan Sistem Informasi Manajemen dan Pelaporan (SIMPEL) Berbasis Website dengan Metode Waterfall - David Fitrianto; Wicaksono Yuli Sulistyo (SIBER PRESS Universitas SIBERMU, 2025)
Lazismu Kebumen Region is a Muhammadiyah Zakat, Infak, and Alms Collection Institution that oversees 23 (twenty-three) Lazismu Service Offices in Kebumen Regency, but data reporting is still manual so it is less efficient and data for all service offices is not centralized in Lazismu Kebumen Region. This study aims to develop a management information system that functions as a centralized data reporting media based on a website by implementing the Laravel and Filament frameworks. The system development process uses the waterfall method, which consists of the stages of needs analysis, system design, implementation, testing and maintenance. The results of the system development that has been carried out run well and contains three main features including the fundraising division, program division and finance division. The results of the Black Box test show that the system functions according to specifications and user satisfaction evaluation of the system is easy to use. This system has been proven to increase the effectiveness of data reporting and make service office data centralized in Lazismu Kebumen Region. The system created has been effective in making reports in Lazismu Kebumen Region and can be adopted by similar institutions to support more effective data reporting. In addition to its practical benefits, this research contributes scientifically to the development of website-based systems and supports more effective management of modern institutions.